2015
DOI: 10.1021/acs.chemmater.5b00885
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-Doped SnO2@Graphene Porous Composite for High Capacity Lithium-Ion Batteries

Abstract: For the first time, a composite of fluorine-doped SnO 2 and reduced graphene oxide (F-SnO 2 @RGO) was synthesized using a cheap F-containing Sn source, Sn(BF 4 ) 2 , through a hydrothermal process. X-ray photoelectron spectroscopy and X-ray diffraction results identified that F was doped in the unit cells of the SnO 2 nanocrystals, instead of only on the surfaces of the nanoparticles. F doping of SnO 2 led to more uniform and higher loading of the F-SnO 2 nanoparticles on the surfaces of RGO sheets, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
102
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(119 citation statements)
references
References 58 publications
10
102
0
6
Order By: Relevance
“…However, our discharge capacity after 100 cycles was 342 mA h g -1 , which is much larger than the theoretical value. Therefore the conversion reactions (13) and (14) may contribute partially in the reversible reaction, which is similar to the case for the LIB. We refer to this as mechanism "B".…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…However, our discharge capacity after 100 cycles was 342 mA h g -1 , which is much larger than the theoretical value. Therefore the conversion reactions (13) and (14) may contribute partially in the reversible reaction, which is similar to the case for the LIB. We refer to this as mechanism "B".…”
Section: Resultsmentioning
confidence: 61%
“…A large number of papers have shown that the use of oxide forms, such as GeO 2 and SnO 2 , can increase the capacity by forming stable solid electrolyte interphase (SEI) layers that mitigate the volumechange stress. [5][6][7][8][9][10][11][12][13] Furthermore, it was suggested that the reversible conversion reaction, GeO 2 (or SnO 2 ) + 4Li + + 4e -↔ Ge (or Sn) + 2Li 2 O, increases the capacities. [6][7][8]11,12 Zn 2 GeO 4 and Zn 2 SnO 4 have recently attracted a great deal of attention since Zn, Ge, Sn, and their oxide forms are all electrochemically active species for lithiation/delithiation.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it confirms the existence of a N‐C skeleton among the small SnO 2 NPs (red arrows), which plays a role in anchoring the active SnO 2 NPs. The lattice fringes with spacings of 0.33 and 0.25 nm correspond to the (110) and (101) planes of SnO 2 , respectively 3f,16. Figure 1 (g) shows the SEM image of the SnO 2 @N‐C hollow nanoclusters, which further illustrates that the SnO 2 @N‐C hollow nanoclusters are well dispersed with spherical morphology.…”
Section: Resultsmentioning
confidence: 89%
“…This type of newly born energy storage technology has drawn tremendous attention. [4][5][6][7][8][9] While much of the previous work focuses on optimizing the performance of energy storage systems, an umber of novel devices have been realized that retain the "primary function" of energy storage systems (that is, energy storage and release on demand), and also incorporate new functionality to create novel types of multifunctional energy storage systems (for example,the smart energy storage system). Ap rototype Al-tungsten oxide electrochromic battery with interactive color-changing behavior is reported.…”
mentioning
confidence: 99%
“…[1] Such systems can mitigate energy shortages and global climate warming issues that the world is currently facing. [4][5][6][7][8][9] While much of the previous work focuses on optimizing the performance of energy storage systems, an umber of novel devices have been realized that retain the "primary function" of energy storage systems (that is, energy storage and release on demand), and also incorporate new functionality to create novel types of multifunctional energy storage systems (for example,the smart energy storage system). [4][5][6][7][8][9] While much of the previous work focuses on optimizing the performance of energy storage systems, an umber of novel devices have been realized that retain the "primary function" of energy storage systems (that is, energy storage and release on demand), and also incorporate new functionality to create novel types of multifunctional energy storage systems (for example,the smart energy storage system).…”
mentioning
confidence: 99%